Control of Vascular Risk Factors and Response to Stroke Symptoms in Argentina During the COVID-19 Quarantine. The SIFHON-COVID Population Survey - Rodríguez Pérez, María S.; Rosales, Julieta S.; Dossi, Daiana E.; Ameriso, Sebastián F. (Frontiers in Neurology, 2022)
Background and objectives: In preparation for the suspected influx of COVID-19 patients, many healthcare systems reduced or discontinued provision of ‘‘non-urgent’’ care. This decision had potential impact on stroke prevention and management. We conducted a large population survey to assess the effect of mandatory social isolation on routine health controls, emergency consultations and other stroke care-related behaviors of the population during the pandemic. Methods: We distributed multiple-choice anonymous questionnaires through the institutional email database and through the email database of clients of a beverage delivery company. Most respondents resided in the metropolitan area of Buenos Aires. This is the area where the infection rates were highest and restriction measures were hardest. The survey assessed demographic characteristics and actual and potential behaviors of people regarding medical checkups, risk factors control, medication provision and response to onset of symptoms consistent with stroke or TIA. Surveys were sent during May 2020, the strictest period of the quarantine in Argentina. Results: A total of 10,303 questionnaires were completed. Thirty-seven percent of the respondents were older than 60 years, 74% were women and 16% lived alone. Vascular risk factors were present in 39% of the individuals. Seventy-six percent did not continue with their regular medical checkups during the mandatory social and preventive isolation, 21% had difficulty obtaining medical prescriptions and only 38% considered that health institutions had implemented reliable safety measures to avoid exposure to COVID-19. When asked about response in case of onset of stroke symptoms, 9% would not consult given the context of the pandemic. Six percent reported having had symptoms consistent with stroke or TIA but only 35% went to a hospital. The vast majority of the respondents said they were awaiting for the end of the quarantine to resume their usual medical care. Conclusions: The implementation of a quarantine may have some serious adverse effects on the prevention, diagnosis and treatment of stroke. These undesirable aspects should be taken into consideration in the planning, communication and implementation of health policies.